This Silence has a Sound...it is the Sound of a Horizon - Antoniou, Klitsa (My University, 2026)
Exhibition : This Silence has a Sound...it is the Sound of a Horizon, ExhibitionTexts: Gabriel Koureas, Hesperia Eliadou, Elena Parpa The Collection Gallery, 2015 Curated by Krista Mikkola